Different Time, Same Place, Same Story? A Social Disorganization Perspective To Examining Juvenile Homicides - Laurikkala, Minna (2009)
In 2007, juveniles were involved in a minimum of 1,063 murders in the United States (Federal Bureau of Investigation, 2008), and a concern over juvenile homicide offenders remains. While increasingly more macrolevel research on juvenile homicide offending has been accumulated, particularly since the 1980s, research focusing on macrolevel correlates of juvenile homicides is still relatively scarce (MacDonald & Gover, 2005; Ousey & Campbell Augustine, 2001). In the first part of this study, several variables relating to the offender, victim, setting, and precursors to the homicide by race and gender were examined in order to provide details on the context of youth homicides between 1965 and 1995 in Chicago. The Homicides in Chicago, 1965-1995 data set and Census data for 1970, 1980, and 1990 were used in this study. The results indicate that changes in youth homicides over the 31-year time period involved increases in lethal gang altercations, particularly among Latinos, and increases in the use of automatic weapons. Young females had very little impact on homicide rates in Chicago. The second part of the study examined whether measures of social disorganization can aid in the prediction of homicides committed by youths, and a total of ten negative binomial models were run. The results of the analyses in the three time periods indicate that racial/ethnic heterogeneity, educational deprivation, unemployment, and family disruption are significantly and positively related to homicides. Foreign-born population and median household income were found to be significantly and negatively related to homicides. The significant indicators of social disorganization varied in the seven models for the disaggregated groups. Overall, the results reflect support for social disorganization theory. Limitations, suggestion for future research, and policy implications are also addressed